Profile of Oral Diseases in Dental Hospital Faculty of Dentistry Universitas Trisakti 2013-2022 - Hartanto, Firstine Kelsi; Amtha, Rahmi; Gunawan, Dika Andiana Sari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Oral health remains a significant concern to date. According to the Riskesdas 2018, the prevalence of oral diseases in Indonesia is high, reaching 57.6%, with 8.2% of cases involving oral mucosal lesions. However, there is a lack of research on the profile of oral diseases, including lesions and oral health conditions, over the past 10 years at the Dental Hospital Faculty of Dentistry Universitas Trisakti. Method: This is a descriptive observational study with consecutive sampling method using secondary data from medical records (unlinked data). Result: A total of 3,266 cases of oral disease were found Dental Hospital Faculty of Dentistry Universitas Trisakti in the period 2013-2022 with a total of 105 types of oral diseases. Oral diseases were mostly found in females (63.68%) in the age group of 15-24 years (28.44%) and from all over Indonesia region, mostly from West Jakarta (8.78%). Most patients had hypertension (3.48%). There was normal variant (45.19%), non-infectious lesion (35.6%), candida infection and related lesion (13.50%), virus infection (5.17%), Oral Potentially Malignant Disease and Oral Squamous Cell Carcinoma (1.74%), halitosis (0.24%), lesions associated systemic diseases (2.54%), and lesions related to psychological condition (1.16%). Conclusion: In 2013-2022 the oral diseases in the Dental Hospital Faculty of Dentistry Universitas Trisakti were varied with the highest amount found in the 2017. The most found were Aphthous Stomatitis (21.92%), Angular Cheilitis (5.20%), Oral Lichen Planus (0.82%), Oral Squamos Cell Carcinoma (0.52%), Cancerphobia (0.45%), and Aphthous-like ulcer (0.39%).